2012
DOI: 10.1029/2012pa002313
|View full text |Cite
|
Sign up to set email alerts
|

Corals record persistent multidecadal SST variability in the Atlantic Warm Pool since 1775 AD

Abstract: [1] Accurate low-latitude sea surface temperature (SST) records that predate the instrumental era are needed to put recent warming in the context of natural climate variability and to evaluate the persistence of lower frequency climate variability prior to the instrumental era and the possible influence of anthropogenic climate change on this variability. Here we present a 235-year-long SST reconstruction based on annual growth rates (linear extension) of three colonies of the Atlantic coral Siderastrea sidere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 54 publications
1
50
0
Order By: Relevance
“…In general, coral growth (annual linear extension) rates in the tropics are found to be negatively correlated with annual mean SST, and this relationship is often used to reconstruct past sea surface temperature (Saenger et al 2009;Cantin et al 2010;Vasquez-Bedoya et al 2012). However, manipulative experiments indicate a parabolic relationship between coral growth (calcification and/or linear extension) and SST (Jokiel and Coles 1977;Jokiel and Coles 1990), with highest growth rates found at temperatures 1 to 2°C below the mean annual maximum.…”
Section: Discussionmentioning
confidence: 99%
“…In general, coral growth (annual linear extension) rates in the tropics are found to be negatively correlated with annual mean SST, and this relationship is often used to reconstruct past sea surface temperature (Saenger et al 2009;Cantin et al 2010;Vasquez-Bedoya et al 2012). However, manipulative experiments indicate a parabolic relationship between coral growth (calcification and/or linear extension) and SST (Jokiel and Coles 1977;Jokiel and Coles 1990), with highest growth rates found at temperatures 1 to 2°C below the mean annual maximum.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach of retrospectively calculating calcification rate, the evidence connecting in situ coral growth to environmental trends is equivocal. Correlation has been demonstrated in some cases, showing declines in coral calcification as the oceans have warmed and acidified (Cooper et al 2008;De'ath et al 2009;Tanzil et al 2009), but in some studies trends were not observed (Helmle et al 2011;Vasquez-Bedoya et al 2012) or observed only on certain reef types (Castillo et al 2011) or regions, with high-latitude reefs even showing increases in calcification with time (Cooper et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the Caribbean, SSTs have risen steadily for the past century (Hoegh-Guldberg, 1999) and according to a modeling study by On annual time scales, thermally induced bleaching and disease have been recognized as the major factors responsible for the large decline in live Caribbean coral cover (Bruckner & Hill 2009;Miller et al 2009) whereas the decline in architectural complexity has largely been associated with an increase in hurricane frequency (Alvarez-Filip et al 2011). On longer, decadal to centennial time scales, the decline in coral growth has been directly associated with the increasing trend in SST (Saenger et al 2009;Vasquez-Bedoya et al, 2012). Because, however, each of these drivers varies in scale, both temporally and spatially, there remains much uncertainty as to which are most responsible for the observed decline in coral …”
Section: Decline Of Caribbean Reefs From 1970-2000mentioning
confidence: 98%
“…Caribbean, most of which find that coral growth rates are decreasing in concert with rising SSTs over the past several decades (Guzman et al 2008, Manzelo et al, 2010, Castillo et al, 2011, Castillo et al, 2012, Vasquez-Bedoya et al, 2012. In Belize, fore-reef colonies of Siderastrea siderea showed a significant decrease in linear extension from 1930-2000, whereas linear extension in colonies on the near shore and back reef showed almost no change (Castillo et al, 2011, Castillo et al, 2012.…”
Section: Numerous Coral Growth Studies Have Been Conducted In the Wesmentioning
confidence: 99%
See 1 more Smart Citation